Formalizing and Verifying a Modern Build Language - Christakis, Maria; Leino, Rustan; Schulte, Wolfram (FM 2014: Formal Methods - 19th International Symposium, Singapore, May 12-16, 2014. Proceedings, 2014)
CLOUDMAKE is a software utility that automatically builds executable programs and libraries from source code—a modern MAKE utility. Its design gives rise to a number of possible optimizations, like cached builds, and the executables to be built are described using a functional programming language. This paper formally and mechanically verifies the correctness of central CLOUDMAKE algorithms. The paper defines the CLOUDMAKE language using an operational semantics, but with a twist: the central operation exec is defined axiomatically, making it pluggable so that it can be replaced by calls to compilers, linkers, and other tools. The formalization and proofs of the central CLOUDMAKE algorithms are done entirely in DAFNY, the proof engine of which is an SMT-based program verifier.